Periodontal intervention effects on pregnancy outcomesin women with preeclampsia (2009)
ABSTRACT: Objective: To determine the efficacy of periodontal intervention on pregnancy outcome in mild preeclamptic women.Methods: A sample of 60 pregnant women with mild preeclampsia (blood pressure levels <160/110 mm and proteinuria>300 mg/l in 24 hours urine) from the Hospital Universitario del Valle (Cali, Colombia) was included to the study. Preeclampticwomen were randomized in two groups, one with periodontal intervention (PIG, N=28) and another in which the periodontalintervention was practiced after childbirth (NPIG, N=32). Maternal socio-demographic, medical and periodontal data wereobtained. PIG included patients in which supragingival and subgingival cleaning within ultrasonic and manual devices wereperformed after study inclusion. The progression from mild to severe preeclampsia, eclampsia or HELLP syndrome, the numberof days of clinical stability and the percentile of birth-weight adjusted for gestational age were evaluated in both groups.Results: Most of the patients (60%) were multigravids. Gestational age at inclusion was 31.8±1.6 weeks. Chronicperiodontitis was a frequent finding (61.7%). Social, demographic, medical and periodontal conditions were similar betweenboth groups. Disease progression to severe preeclampsia, eclampsia or HELLP syndrome was also similar (89.2% PIG versus84.4%, p=0.65) (OR=1.06 IC 95% 0.87-1.29, p=0.65). Days of clinical stability were similar between the groups (median 10 days, range 1-46, PIG versus 12 days, range 1-59, p=0.57) and the percentile of birth weight adjusted with gestational age had nodifferences between the groups (median percentil 50 range 5-90 PIG versus percentil 55 range 5-95, p=0.73).Conclusion: Periodontal intervention does not seem to harm the health, the severity or alter the frequency on maternalcomplications in mild preeclampsia subjects.